A case of KIT negative extra-gastrointestinal stromal tumor arising in the greater omentum with predominant cystic formation - Katsuya Nanjo, MD (Radiology Case Reports, 2021)
We report a rare case of KIT-negative extra-gastrointestinal stromal tumor, in a 40-year-old woman. Contrast-enhanced computed tomography and magnetic resonance imaging revealed a >15-cm mass of multiple cystic lesions in the greater omentum. Histopathological findings after surgery showed a sheet-like growth of stellate tumor cells from epithelial cells, cystic degeneration, and mucus-like stroma. Immunohistochemistry was positive for discovered on GIST-1 (DOG1) but negative for CD117 (c-kit).